Diagnosis of rheumatoid arthritis by a complex radionuclide study of the joints - Pekhlivanov, D N; Mlŭchkov, Kh (Vutreshni bolesti, 1980)
The knee joints of 88 patients with rheumatoid arthritis and 22 healthy subjects were examined via a complex radiometric method. The time for half-elimination of 133xenon, injected into the joints, is 154.8 minutes for the control group and 118.7 min, 81.6 min and 39.2 min according to the graded activity of rheumatoid arthritis. The accumulation of 99mTc-pertechnetate is 115.3% for the controls and 131.0%, 151.0% and 178.0% for the joints with inflammatory reaction. The accumulation of 99mTc-pyrophosphate is 115.7% and 133.0%, 149.9% and 170.7% respectively in the patients with I, II and III degree of rheumatoid arthritis activity. The manifestation of X-ray signs of osteo-articular destruction is combined with higher radionuclide indices than those corresponding to rheumatic activity. The results reveal an enhanced reactivity of all articular structures (synovial sac, bone-epiphyses) in the patients with rheumatoid arthritis. The following radio-isotope constellation is indicated for the early diagnostics and differential diagnosis in case of that disease: high effectiveness of articular 133xenon clearance, equivalence of figure expression and similarity in the changes of the depots 99mTc-pertechnetate and 99mTc-pyrophosphate in the knee joints of patients with rheumatoid arthritis.